Femur fractures in the elderly in Northeast Brazil: epidemiological data and expenses for the SUS (Research, Society and Development, 2021)
Objectives: to evaluate epidemiological data including incidence, age group, sex, color / race, mortality, average hospital stay and expenses of the Unified Health System (SUS) related to femur fractures in the elderly (≥60 years) in the Northeast of Brazil. Methods: descriptive study based on secondary data from the Hospital Information System of the Unified Health System (SIH / SUS). In the DATASUS platform, filters were selected that represent the study variables related to the period from January 2019 to December 2020. The incidence calculations were made based on the population of the Northeast region defined by the 2010 IBGE census. Results: there were 24,239 hospitalizations for femur fractures during the time period studied. The mean annual incidence was 22.22 cases per 10,000 elderly people in the Northeast. These figures generated a total cost for the SUS of R $ 62,713,218.03. People aged 80 years and over were the majority, with 48.17% of income. Women had 2.2 times more hospitalizations than men. Men had a higher mortality rate, 3.97%. Browns accounted for the majority of admissions. Indigenous and whites had higher mortality. Conclusion: femur fractures have a high incidence in the elderly in northeastern Brazil and generate costly expenses for the health system.